Menggali Penyebab Tingginya Kasus Penularan Penyakit Seksual di Kabupaten Kuningan Perspektif Ham dalam Peraturan Bupati No 362 Tahun 2022 - Widiawati, Siska (UM Purwokerto Press, 2024)
Transmission of sexually transmitted diseases and HIV/AIDS is a public health problem that is still a global challenge. This article aims to analyze the factors causing the transmission of sexually transmitted diseases and stigma towards people with HIV/AIDS, and to examine solutions that support human rights. The results of the analysis show that social, economic, cultural, and structural factors, such as poverty, gender inequality, and limited access to health information and services, increase the vulnerability of certain community groups to the transmission of sexually transmitted diseases. Meanwhile, widespread stigma and discrimination in society have robbed the basic rights of people with HIV, especially the right to health, work, and social participation. This article suggests a human rights-based approach as a comprehensive solution. Preventive and treatment interventions carried out, legal protection and anti-discrimination policies, empowerment of communities and vulnerable groups, and increasing government accountability. The implementation of these solutions is expected to address the root of the problem and encourage the fulfillment of human rights related to sexual and reproductive health. The conclusions obtained in this study include efforts to increase access to comprehensive health services, accompanied by effective public education campaigns. In addition, legal and policy reforms that respect the human rights of people with sexually transmitted diseases are also important steps to address stigma and discrimination.